2006
DOI: 10.1080/10503300600589456
|View full text |Cite
|
Sign up to set email alerts
|

The effects of adding emotion-focused interventions to the client-centered relationship conditions in the treatment of depression

Abstract: Does it work in the real world? The effectiveness of treatments for psychological problems in children and adolescent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
138
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(153 citation statements)
references
References 23 publications
3
138
0
2
Order By: Relevance
“…At least, authors concluded that EFCT increased intimacy in the experimental group as compared to the control group. Goldman, Greenberg and Angus [32] examined the effects of adding emotion-focused interventions to the client-centered relationship conditions in the treatment of depression.…”
Section: Discussionmentioning
confidence: 99%
“…At least, authors concluded that EFCT increased intimacy in the experimental group as compared to the control group. Goldman, Greenberg and Angus [32] examined the effects of adding emotion-focused interventions to the client-centered relationship conditions in the treatment of depression.…”
Section: Discussionmentioning
confidence: 99%
“…La Accurate Empathy Scale ha sido una de las m谩s utilizadas para la investigaci贸n de la empat铆a. Se ha aplicado para investigar sobre formaci贸n de terapeutas (Reyes y Benitez, 1991), as铆 como para la identifi caci贸n de las diferencias en empat铆a entre diferentes tipos de terapias (Goldman, Greenberg, y Angus, 2006). Ha supuesto tambi茅n una importante herramienta de entrenamiento con la que ense帽ar la practica de la exactitud o precisi贸n emp谩tica.…”
Section: Interpersonal Process Recall (Ipr;unclassified
“…As Burckell and McMain reported, approximately 36% of individuals diagnosed with BPD fail to respond to DBT (Salsman, Harned, Secrist, Comtois, & Linehan 2008). In reporting the results of two outcome studies comparing EFT against client-centered therapy, Goldman, Greenberg, and Angus (2006) explained that at post-treatment, 5 (14%) clients were depressed, while 86% were in remission, among which 25 (69%) were considered to be recovered. Although both therapies are notably successful, there is still a need to improve upon both treatments.…”
Section: Case Comparisons For Dialectical Behavior Therapy (Dbt) and mentioning
confidence: 99%